Could persistent organic pollutants affect future generations of sea turtles by maternal transfer? First results for Caretta caretta nests along the North-Western coast of Italy - Ceciarini, Ilaria; Capanni, Francesca; Minoia, Lorenzo; Consales, Guia; Amico, Carlo; Zuffi, Marco Alberto Luca; Terracciano, Giuliana; Mancusi, Cecilia; Neri, Alessandra; Franchi, Enrica; Raimondi, Giovanni; Prestanti, Alessia; et al. (Frontiers in Marine Science, 2024)
Since 2013, loggerhead sea turtle (Caretta caretta, Linnaeus 1758) nesting has been observed further north along the Italian coast, reaching the Tuscan coast (NW Mediterranean Sea). The four nesting events occurred in Tuscany in summer 2019 spurred the scientific community to monitor these occurrences more carefully following them from egg deposition to hatching. This provided an opportunity to collect samples for conducting multidisciplinary investigations, including the toxicological investigations of the biological material collected from the four nests. The aim of this study was to conduct an initial assessment of persistent organic pollutants in the eggs laid in Tuscany, aiming to establish a baseline on this topic for subsequent nesting events that have occurred until nowadays. Organochlorine compounds (OCs), specifically polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethane and its metabolites (DDTs), and hexachlorobenzene (HCB) were analysed and detected in unhatched eggs, embryos, and chorio-allantoic membranes (CAM). OCs were detected in all samples, with PCBs>DDTs≫HCB. A significant spatial variation in pollutant levels and profiles among sea turtle nesting locations was found. Embryos showed higher level of contamination than egg contents regardless of the developmental stages. Depth in the laying chamber and egg mass were not significant factor in OCs bioaccumulation. For the first time in the Mediterranean Sea this study assessed the role of CAM in the transfer of contaminants to the embryo. Overall, the OC levels found were lower compared to the results from other studies conducted worldwide in loggerhead sea turtle biological material. This was the first assessment in nest biological material for the North-Western coast of Italy.